ANALISIS YURIDIS PENANGKAPAN IKAN TANPA SIUP DAN SIPI OLEH KAPAL BERBENDERA ASING - Keiko Hauriza Setiawan; Dyah Setyorini (Fakultas Hukum Universitas Trisakti, 2022)
Every individual or corporation engaged in the fishing industry is required to hold a permit. It is intended that by granting this licence, fishing operations will be legally protected and that fish resources will remain abundant. The Job Creation Law and Law No. 31/2004 concerning Amendments to Law No. 31 of 2004 Concerning Fisheries (hereinafter referred to as the Fisheries Law) very clearly regulate licenses for fishing activities, but PERMEN Maritime Affairs and Fisheries No. 17/2006 concerning Capture Fisheries Businesses regulates licenses for fishing activities for Indonesian-flagged vessels then changed the Minister of Maritime Affairs and Fisheries Regulation No. 58/2020 concerning Capture Fisheries Businesses, providing licenses to vessels flying the Indonesian and foreign flags, Fishing by foreign-flagged vessels without a Fishery Business Permit (SIUP) and Permit Fishing (SIPI) is clearly illegal and in violation of Articles 26 and 27 of the Fisheries Law. It may also be subject to Article 92 of the Fisheries Law.